OUTCOME OF INTERLOCKING NAILING IN HUMERAL SHAFT FRACTURE: A LONGITUDINAL STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Introduction: Fractures of shaft of humerus are a major cause of morbidity, especially with increasing vehicular traffic and rising incidents of road traffic accidents (RTA). While conservative management is associated with higher morbidity and high rates of non-union, open reduction is often associated with postoperative pain, soft tissue and neurovascular injury. With carefully selected patient, proper operative procedure and planned postoperative rehabilitation, the postoperative complications and morbidity following intramedullary nailing may be minimized. Therefore, the present study was conducted to assess the effectiveness of intramedullary nailing in patients with fracture of shaft of humerus. Materials and methods: This prospective, interventional study was conducted after obtaining approval from the Institutional Ethics Committee. A total of 62 patients with radiologically confirmed fracture of shaft of humerus were included in the study, provided they met the inclusion and exclusion criteria and provided voluntary, written and informed consent. Demographic details and relevant histories were noted. Intramedullary interlocking nailing was done under aseptic precautions. Postoperatively, physiotherapy was done with shoulder and elbow exercises. The patients were followed up till 6 months postoperatively and radiological and functional outcomes were assessed. Results: In the present study, the mean age of the patients was 42.6 ± 10.4 years with a male preponderance (43 patients, 69.35%). Right sided injury (52 patients, 83.87%) was commonly seen. 61.29% (38 patients) had recovered within 8 to 16 weeks. 40 patients (64.52%) had no complications. Excellent to moderate radiological outcome was seen in 95.61% patients. Poor functional outcome was observed in 3 patients (4.84%) in terms of range of motion (ROM) and 4 patients (6.45%) in terms of Visual Analog Scale (VAS) score. Conclusion: Intramedullary interlocking nail is an effective and less invasive treatment modality for fractures of shaft of humerus. It has lower complication rates with no incidence of postoperative wound infection and favourable recovery profile. Careful selection of patient coupled with proper intraoperative procedure and planned postoperative rehabilitation results in good recovery rates, in terms of both, radiological and functional outcomes.